Compression engineering of sports garments using athletes' anthropometric data/3D scanning technologies - Azam, Z.; Brubacher, K.; Gill, S.; Fernando, A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This research aims to develop sport compression garments (SCGs) for athletes and with the required compression. Graduated compression thigh-high socks were designed for the Alva-40 mannequin, and compression was measured using picopress instrument. The anthropometry of the mannequin and six male scans were analysed using 3D scanning size stream software. The compression results were modelled for six scans through fabric stress to strain (found through tensile testing) on the body using its dimensions and compared to mannequins with scans of similar dimensions at the ankle. Results found dimension variation randomly at different points for scans, leading to compression that was not progressive for modelled results. It concludes that wearing compression garments designed for one body has varying compression on other bodies.